Burns in South Korea: An analysis of nationwide data from the Health Insurance Review and Assessment Service. Issue 3 (May 2016) - Oh, Hyunjin; Boo, Sunjoo
Highlights: Epidemiological information regarding characteristics of burns is limited in Korea. We analyze population-based data to evaluate the characteristics of burned patients. People in South Korea experience higher numbers of burns than other countries. General burn prevention programs are needed to reduce the risk of burns. Abstract: Introduction: The purpose of the study was to identify and describe the incidence of burn injuries in patients seen and treated in South Korea. Characteristics of inpatients and outpatients with burns were analyzed according to gender, age, burn site, and burn severity. Methods: This retrospective study examined the characteristics of a stratified sample of burn patients seen and treated in South Korea during the calendar year 2011. The sample was drawn from the national patient database Health Insurance Review and Assessment (HIRA). Results: Approximately 1.71% of the total patients in the Patient Sample of HIRA for 2011 were burn-injured patients. The numbers of patients treated for burns were 913/10 5 males ( n = 8009) and 1454/10 5 females ( n = 11, 881). Nearly all of these patients (94.1%) were covered by national health insurance and the majority of these patients (80.6%) were treated as outpatients. Nearly half of the burn injuries were of the upper extremities (43.5%), and most of these injuries (71.5%) were rated as second-degree burns. Conclusion: A review of the national data on patients seen and treated for burns in 2011 revealed that people in South Korea may experience higher numbers and more severe cases of burns and burn-related injuries than found in other countries. General burn prevention programs as well as gender- and age-specific prevention strategies are needed to reduce the risk of burns in this population.